Effects of sodium chloride on germination, growth, relative water content, and chlorophyll, proline, malondialdehyde and vitamin C contents in Chinese white radish seedlings (Raphanus sativus L. Var. Longipinnatus bailey) - Jarunee Jungklang (2018)
© 2018 by Maejo University, San Sai, Chiang Mai, 50290 Thailand. Effects of sodium chloride (NaCl) on germination, growth, relative water content (RWC), as well as chlorophyll, proline, malondialdehyde (MDA) and vitamin C contents in the seedlings of Chinese white radish specimens (Raphanus sativus L. var. longipinnatus Bailey) were investigated. The seeds were sown on fine sand culture for 7 days. Fifty mL of NaCl solution at concentrations of 0, 100 and 200 mM were applied to the culture each day during the length of the experiment for 7 days, resulting in the electrical conductivity (using 1:5 soil:water method) of the sand culture being at 0.06-0.07, 0.4-0.8 and 0.8-1.6 dS/m respectively. Specific parameters, viz. germination, growth, RWC, and chlorophyll, proline, MDA and vitamin C contents of the shoots of 7-day-old seedlings, were evaluated. The results show that 100 mM NaCl increases the shoot fresh weight while other parameters show the same tendency when compared to the control. Conversely, 200 mM NaCl significantly decreases germination, growth, RWC and chlorophyll content but increases proline, MDA and vitamin C contents by 132%, 53% and 82% respectively when compared to the control.